Effects of cold exposure revealed by global transcriptomic analysis in ferret peripheral blood mononuclear cells - Reynés, Bàrbara (Sci Rep, 2019)
Animal studies, mostly performed in rodents, show the beneficial anti-obesity effects of cold studies. This is due to thermogenic activation of brown adipose tissue (BAT), a tissue also recently discovered in adult humans. Studies in humans, however, are hampered by the accessibility of most tissues. In contrast, peripheral blood mononuclear cells (PBMC) are accessible and share the expression profile of different sets of genes with other tissues, including those that reflect metabolic responses. Ferrets are an animal model physiologically closer to humans than rodents. Here, we investigated the effects on ferrets of one-week acclimation to 4 °C by analysing the PBMC transcriptome. Cold exposure deeply affected PBMC gene expression, producing a widespread down-regulation of genes involved in different biological pathways (cell cycle, gene expression regulation/protein synthesis, immune response, signal transduction, and genes related to extracellular matrix/cytoskeleton), while thermogenic and glycogenolysis-related processes were increased. Results obtained in PBMC reflected those of adipose tissue, but hardly those of the liver. Our study, using ferret as a model, reinforce PBMC usefulness as sentinel biological material for cold-exposure studies in order to deepen our understanding of the general and specific pathways affected by cold acclimation. This is relevant for future development of therapies to be used clinically.